Σάββατο, 2 Ιουλίου 2016

Εις το τετράγωνο

Nα λυθεί η εξίσωση

$2^2+3^2+6^2=(2+3+χ)^2$.

 Διασκεδαστικά Μαθηματικά    www.eisatopon.blogspot.com     

3 σχόλια:

  1. 2^2+3^2+6^2=(2+3+χ)^2
    2^2+3^2+6^2=2^2+3^2+χ^2+2*2*3+2*3*χ+2*χ*2
    4+9+36=4+9+χ^2+12+6χ++4χ
    49=χ^2+10χ+25
    χ^+10χ-24(1)
    χ=-10+/-sqrt[(10)^2)-4*1*(-24)]/2*1
    χ=-10+/-sqrt[100+96]/2
    x=-10+/-sqrt[196]/2
    x=(-10+/-14)/2
    x1=(-10+14)/2 ---> x1=4/2 ---> x1=2
    x2=(-10-14)/2 ---> x2=-24/2 ---> x2=-12
    Επαλήθευση:
    2^2+3^2+6^2=(2+3+χ)^2
    2^2+3^2+6^2=(2+3+2)^2
    4+9+36=7^2
    49=7^2

    ΑπάντησηΔιαγραφή
  2. Επίσης:
    Επαλήθευση:
    2^2+3^2+6^2=(2+3+χ)^2
    2^2+3^2+6^2=(2+3-12)^2
    4+9+36=(-7)^2
    49=(-7)^2

    ΑπάντησηΔιαγραφή
  3. Ξέηχασα να γράψω στην εξίσωση (1) ότι ισούται με μηδέν (0).
    χ^+10χ-24=0(1)

    ΑπάντησηΔιαγραφή